Partnership funding in flood risk management: new localism debate and policy in England. Issue 4 (4th November 2014) - Thaler, Thomas; Priest, Sally
<x xml:space="preserve">Abstract</x> The new flood risk policy discussion in England has started to redefine national policy regarding flood and coastal risk management. The key issue in the new policy agenda is to encourage the responsibilities of local authorities in flood risk management, which involve defining local strategies to manage local risks. This downscaling process in flood risk management has a series of consequences in the development of new governance structures and institutions as well as new working relations and intervention strategies. Nevertheless, the main problem is the gap between the downscaling of responsibility and the transfer of resources; in particular the question concerning funding and social capacity. In this way, the focus of policy discussion refers to two main aspects: (a) the equitable sharing of risk‐burdens between public authorities, private companies and individuals and (b) how to encourage government agencies and nongovernment agents to take over responsibility for certain tasks from central government. The aim of this paper is to discuss the new funding regime for English flood risk management policy under the new policy paradigm.